2020
DOI: 10.1007/978-3-030-56880-1_12
|View full text |Cite
|
Sign up to set email alerts
|

LWE with Side Information: Attacks and Concrete Security Estimation

Abstract: We propose a framework for cryptanalysis of lattice-based schemes, when side information-in the form of "hints"-about the secret and/or error is available. Our framework generalizes the so-called primal lattice reduction attack, and allows the progressive integration of hints before running a final lattice reduction step. Our techniques for integrating hints include sparsifying the lattice, projecting onto and intersecting with hyperplanes, and/or altering the distribution of the secret vector. Our main contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 23 publications
1
49
0
Order By: Relevance
“…In particular, it would be interesting to implement our correction of [BPO + 20] to investigate the final performance to compare the results with other approaches. Additionally, it would be interesting to investigate improvements or generalizations of the framework provided in [DDGR20] to reduce the number of required approximate linear equations. A good understanding of the cost of retrieving the full secret could help to bound the amount of side-channel leakage an attacker would be allowed to obtain in a realistic scenario.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, it would be interesting to implement our correction of [BPO + 20] to investigate the final performance to compare the results with other approaches. Additionally, it would be interesting to investigate improvements or generalizations of the framework provided in [DDGR20] to reduce the number of required approximate linear equations. A good understanding of the cost of retrieving the full secret could help to bound the amount of side-channel leakage an attacker would be allowed to obtain in a realistic scenario.…”
Section: Discussionmentioning
confidence: 99%
“…This compression prohibits gaining exact equations in the secret in our case, which diminishes the information we retrieved from the oracle. To counter this, we show that we can still retrieve approximate equations in the secret key which, combined with the leaky-LWE framework of Dachman-Soled et al [DDGR20], allows to effectively retrieve the secret key.…”
Section: Attackmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Dachman-Soled et al [DDGR20] showed how such probabilities (soft information) can be incorporated into a lattice-reduction approach. There, however, it is important that the probabilities are somewhat reliable.…”
Section: Future Workmentioning
confidence: 99%